Capturing Finance : Arbitrage and Social Domination - Hardin, Carolyn F., 1979- (Book collections on Project MUSE., 2021)
"Carolyn Hardin offers a new way of understanding arbitrage-the trading practice that involves buying assets in one market at a cheap price and immediately selling them in another market for a profit-as a means of showing how its reliance upon taking on risk is fundamental to financial markets."--